RETENSI KAROTEN DAN RETINOL PALMITAT PADA MINYAK GORENG DAN PRODUK GORENGANNYA - Hasrul Abdi Hasibuan (Pusat Penelitian Kelapa Sawit, 2016)
Fortification of vitamin A in the cooking oil needs to be revisited given that the used oil is palm oil and fortificant form of vitamin A or retinol palmitate have to be imported. On the other hand, palm oil contains carotene as pro-vitamin A and potentially as an alternative of fortificant. The aim of this study was to compare the retention of carotene to retinol palmitate in palm cooking oil and the products fried in the oil using deep frying at 150°C. Materials used as fried products were potatoes, tofu and chicken. The quality of cooking oil that determined were the fatty acid composition, water content, free fatty acid, peroxide value, color, retention of carotene and retinol palmitate. While the quality of the products fried in the oil that determined were water, fat, carotene and retinol palmitate content. The results of this study showed that fortificant (carotene and retinol palmitate) no significant difference to the quality of cooking oil except color, retention of carotene and retinol palmitate. Fortificants also showed no significant difference to the quality of fried products. Retention of carotene showed significantly decreased with increasing frying repeatedly, but had a higher retention and significantly different than retinol palmitate. Retention of carotene in the frying pan first, second, third, fourth and fifth were in the range of 86-89%, 83-89%, 80-83%, 77-80% and 77-80%, while retinol palmitate were 68-100%, 58-97%, 51-89%, 50-84%, and 40-75%. Thus, carotene can be used as an alternative of fortificant in the palm cooking oil.